Transformasi Penyuluhan Agama di Era Society 5.0: Analisis Pemanfaatan Teknologi Digital Melalui Difusi Inovasi - Yosep Sudarso; Harun Y. Natonis (JOURNAL SAINS STUDENT RESEARCH, 2025)
Digital transformation of religious outreach is an inevitability of the times. In reality, some religious instructors are not yet ready due to various obstacles. By analyzing the theory of innovation diffusion, this article aims to lay a conceptual foundation and provide an academic call for religious instructors to transform their duties and functions. The method used is literature research. The results show that innovation diffusion theory is highly relevant. Digital religious outreach has relative advantages, compatibility, complexity, trialability, and observability. This new style of outreach also has unique communication channels. From a time and social system perspective, this theory serves as a warning for religious instructors and related stakeholders to act anticipatively and provide solutions, especially in dealing with the challenges still faced by society in the Society 5.0 era. Ultimately, this study encourages religious instructors to improve their competency in both digital literacy and academic studies relevant to their duties and functions.